Role of Cholestyramine in Refractory Hyperthyroidism: A Case Report and Literature Review - Alswat, Khaled A. (Am J Case Rep, 2015)
Patient: Female, 52 Final Diagnosis: Refractory iodine induced hyperthyroidism Symptoms: Neck swelling • shortness of breath Medication: Cholestyramine Clinical Procedure: Total thyroidectomy Specialty: Endocrinology and Metabolic OBJECTIVE: Unusual clinical course BACKGROUND: Hyperthyroidism is a common disease that usually responds to the conventional therapy of anti-thyroidal medications (methimazole or PTU) and beta-blocker. Refractory hyperthyroidism is a rare condition in which hyperthyroidism fails to respond to the above therapy. Cholestyramine has been shown to decrease thyroid hormone level when added to the ongoing anti-thyroidal medications. CASE REPORT: A 52-year-old woman with past medical history of enlarging goiter presented with obstructive symptoms of worsening shortness of breath and snoring. Admission thyroid function test showed mild hyperthyroidism (suppressed TSH, slightly high FT4, and high normal FT3) that worsened after she received a CT scan with contrast and failed to respond to a 3-week course of high-dose dexamethasone, high-dose carbimazole, and up-titrated propranolol. Five days after cholestyramine was added, her FT4 decreased by 30% and normalized after 12 days. The patient underwent total thyroidectomy as definitive treatment for the hyperthyroidism and for the obstructive symptoms. CONCLUSIONS: Cholestyramine is an effective additional treatment for hyperthyroidism and may be an effective treatment for refractory iodine-induced hyperthyroidism. The possibility of self-remission (natural course) is less likely given the dramatic and rapid response to cholestyramine.